PENGARUH JANUARY EFFECT DAN ROGALSKI EFFECT TERHADAP ABNORMAL RETURN SAHAM DAN TRADING VOLUME ACTIVITY (Studi Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia) - Karina Maliasari; Nur Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The research aims: to test the influence of January Effect and Rogalski Effect of the Abnormal Return and Trading Volume Activity in the Indonesia stock exchange. The sample was selected by using purposive sampling technique. Methods of analysis used the Product Moment Correlation Test, Kruskall-wallis Test, Paired Sample t-Test, and Wilcoxon Signed Rank Test. The result showed that January Effect occurs in the period 2012 influential against to Abnormal return but it didn’t happen, further more influence on Trading Volume Activity. But Rogalski Effect didn’t exist in the Indonesia stock exchange. Keywords:January effect, Rogalski effect, abnormal return, trading volume activity, LQ45 stock price index